Characteristics of genetic and phenotypic properties of tick-borne encephalitis virus strains isolated from various source on the territory of Eastern Siberia - M. M. Verkhozina (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Since ixodid ticks and their feeders (vertebrates) form the basis of the tick-borne encephalitis virus (TBEV) population, it was interesting to obtain a genetic characteristic of strains isolated from various sources in the territory of Eastern Siberia. In our study, it was found that the circulation of TBEV of genotypes 1, 2, 3, 5 and "polytypic" strains in the territory of Eastern Siberia is maintained both by the main vectors (I. persulcatus ticks) and by their feeders (small and large mammals, birds). The distribution of genotypes in strains groups from ixodid ticks and vertebrates varied. TBEV strains of genotypes 1 and 2 were significantly more often isolated from rodents, and genotype 3 from ixodid ticks (p < 0.05). Isolates of genotype 3 (85.5 %) prevailed in the group of strains isolated from ixodid ticks, of which 29.6 % belonged to "Vasilchenko", and 25.6 % to "Zausaev"subgenotypes. Genotypes 1 and 2 were represented by single isolates (3.3 % and 1.3 %, respectively). Among strains isolated from warm-blooded hosts, the proportion of genotype 1 was 35.3 %, genotype 2 -11.8 %, genotype 3 - 35.3 %. More than half of genotype 3 strains (58.3 %) were related to "Vasilchenko" subgenotype, and the strains of "Zausaev" subgenotype were not detected. The obtained data suggest that ixodid ticks and warm-blooded animals are amplifiers of TBEV of genotypes 3 and 1, respectively. The certain differences in the phenotypic characteristics of strains isolated from ticks and warm-blooded animals have been revealed. It has been found that strains isolated from ticks are more homogeneous in their antigenic characteristics, less heterogeneous in S-feature than strains isolated from warm-blooded sources. The strains isolated from warm-blooded animals demonstrate somewhat greater resistance to warming but reducing the reproduction of the virus at 42 °C, and have greater virulence compared to strains isolated from ticks.